2015
DOI: 10.1161/hypertensionaha.115.05440
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Blood Pressure Variability Relates to the Presence of Subclinical Brain Small Vessel Disease in Primary Hypertension

Abstract: C urrent guidelines recommend the assessment of vascular risk factors, target organ damage, and blood pressure (BP) levels to guide the treatment on primary hypertension.1 Besides BP levels, other BP-related features, such as the nocturnal dipping 2 or more recently, visit-to-visit or long-term BP variability (BPV), have been independently associated with clinical cardiovascular outcomes in a recent systematic review and meta-analysis. 3 Also, the prognostic value of BPV measured with ambulatory BP monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 38 publications
3
73
2
6
Order By: Relevance
“…The study also found that lacunar infarction was significantly associated with cognitive impairment and that only ARV differed significantly between subjects with and without cognitive decline. Similarly, Filomena et al conducted a cohort study on asymptomatic hypertensive patients to evaluate the potential usefulness of BPV as a predictor of CSVD, compared with BP and other clinical factors . Only BPV, measured as ARV, was independently related to the presence of CSVD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that lacunar infarction was significantly associated with cognitive impairment and that only ARV differed significantly between subjects with and without cognitive decline. Similarly, Filomena et al conducted a cohort study on asymptomatic hypertensive patients to evaluate the potential usefulness of BPV as a predictor of CSVD, compared with BP and other clinical factors . Only BPV, measured as ARV, was independently related to the presence of CSVD.…”
Section: Resultsmentioning
confidence: 99%
“…Although ARV has been shown to be a better predictor of risk than SD for most adverse outcomes, studies to date have not estimated ARV using real‐time monitoring, because no existing ABPM devices incorporate automatic quantification of ARV or other novel BPV indexes. The procedures for collection, computation, and storage of electronic BP recordings need to automatically provide accurate calculations of 24‐hour BPV.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a fluctuation or variability in blood pressure was related to the presence of cerebral SVD [30]. Therefore, these fluctuations could cause shearing forces to the cerebral vasculature, and these shearing forces could injure arterioles leading to cerebral SVD.…”
Section: Discussionmentioning
confidence: 98%
“…Underlying vascular pathologies are arteriolosclerosis, lipohyalinosis, fibroid necrosis, oedema and damage to the blood-cerebrospinal fluid and blood–brain barriers (BCB/BBB), the latter resulting in chronic leakage of fluid and macromolecules in the white matter and inflammation (reviewed by Kalaria, 2016) [5]. Although SSVD pathogenesis remains poorly understood, it is an age-related condition, associated with a number of risk factors including systemic hypertension [69], chronic kidney disease [10, 11], smoking [12], metabolic syndrome [8, 13, 14], osteoporosis [15], chronic obstructive pulmonary disease [16] and sleep-apnoea syndrome [17]. The SSVD clinical manifestations are largely due to complete (lacunes) or incomplete (WML) infarction(s) and microbleeds resulting in cognitive, motor and mood disturbances and eventually functional disability [2], although same lesions might appear in cognitively intact persons during normal ageing.…”
Section: Methodsmentioning
confidence: 99%